Estimation of S-wave velocity structure and its application to ground motion simulation - Kafle, Basant; Yamanaka, Hiroaki (Journal of Nepal Geological Society, 2002)
Microtremor array is the most inexpensive and easy to perform technique for the estimation of S-wave velocity structure. Microtremor array measurements have been carried out in the Shizuoka Prefecture, Japan to estimate S-wave velocity structure up to the basement. Phase velocities at wide period range were determined by frequency-wavenumber spectral analysis of vertical microtremor array records. The determined phase velocity is inverted to obtain one-dimensional S-wave velocity profile by genetic algorithm inversion method. A four layer S-wave velocity model with a basement velocity of 3.5 km/s was constructed. Simulation of ground motion has been carried out with two-dimensional finite difference method. Simulation of subsurface structural model was derived from the microtremor array measurement and previous seismic refraction survey. Two profiles were taken for simulation one from Hamaoka to Ryuhyoh and another from Hamaoka to Shimada. 2-D effect of subsurface structure is observed in the propagation of ground motion in the basin. The importance of determination of 2-D subsurface structure for the estimation of ground motion is shown.